2017
DOI: 10.3390/s17050992
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Determination of TNF-α for Early Diagnosis of Neonatal Infections with a Novel and Reusable Electrochemical Sensor

Abstract: Early diagnosis is vital for the reduction of mortality caused by neonatal infections. Since TNF-α can be used as a marker for the early diagnosis, the detection of TNF-α with high sensitivity and specificity has great clinical significance. Herein, a highly sensitive and reusable electrochemical sensor was fabricated. Due to the high specificity of aptamers, TNF-α could be accurately detected from five similar cytokines, even from serum samples. In addition, Au nanoparticles (AuNPs) with a high surface area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…[2][3][4][5][6] This view has been substantiated largely by studies in which elevated TNFα levels have been reported in patients with cancer treated with DOX. [7][8][9] However, the relationship between TNFα and DOX cardiotoxicity remains cryptic. TNFα can drive innate signaling by pathogen-activated molecular programs, as well as damage-activated molecular programs.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] This view has been substantiated largely by studies in which elevated TNFα levels have been reported in patients with cancer treated with DOX. [7][8][9] However, the relationship between TNFα and DOX cardiotoxicity remains cryptic. TNFα can drive innate signaling by pathogen-activated molecular programs, as well as damage-activated molecular programs.…”
mentioning
confidence: 99%
“…Then, SiNWs were immersed in an aqueous solution of HF and AgNO 3 under the optimal conditions found in our previous study devoted for rhodamine 6G detection [26]. The AgNPs/SiNWs were further functionalized with a densely packed self-assembled layer of hexanethiol, to avoid nonspecific binding of the analyte on the surface, by incubating the SERS substrate in 10 -3 M of MCH [29,30]. Since the arrangement of the thiolated DNA on sensor surfaces has a deep impact on molecular recognition [31], the thiol-terminated DNA aptamer (anti-PSA) was tethered to the surface by exchanging with already adsorbed thiols through immersing MCH/AgNPs/SiNWs substrate (11 cm 2 wafer) in 2 mL of 1 µM of anti-PSA aptamer dissolved in PBS for 4, 8, 12 and 16h at RT.…”
Section: Bioplatform Assembly and Operationmentioning
confidence: 99%
“…Platinum, which is often alloyed with Iridium, is commonly used for clinical applications and is recognized to be durable and safe over long periods of time. Platinum however, has a relatively low CIC (Leung et al, 2015 ), other emerging materials such as various forms of Iridium Oxide and poly (3,4-ethylenedioxythiophene) (PEDOT) have CIC values of roughly 20x to 100x (respectively) as that of Platinum (Cogan, 2008 ), and are good candidates for the microelectrodes required for accessing targets in mice. Validation of the durability of these materials is ongoing (Straka et al, 2018 ; Dijk et al, 2019 ).…”
Section: Technical Challengesmentioning
confidence: 99%